BELENGGU TENGKULAK ATAS PETANI PEMBUDIDAYA LELE: Relasi Patron-Klien Budidaya Lele Di Wonotunggal Jawa Tengah - Iwan Zaenul Fuad; Aenurofik Aenurofik; Ahmad Rosyid (Jurnal Hukum Islam, 2015)
Within the context of Indonesia as a muslim majority country, Islamic teaching has been widely implemented throughout the country. As a result, Islamic values have become the foundation and basic values within societal economic practices. These values, among others, include social and economic justice and equality. However, these values are not always implemented when people's injustice and greed are in play. One of the cases that can provide example in this case is the relationship between catfish farmers and distributors in Wonotunggal, Batang, Central Java. As a commodity with high economical value, many farmers grow catfish. Thus, there was a big need for catfish distributors to facilitate the rising numbers of catfish farmers, to help them sell the catfish. However, there were many distributors who made attempt to control the market, which give disadvantages to the farmers. One of the examples of such disadvantageous practices is 'ijon', or lending money to the farmers with high interest. As a result many farmers were trapped into debt. This study aims at exploring the relationship between catfish farmers and distributors in Siwatu Village, Wonotunggal, Batang.